(untitled) (Applied Biological Research, 2024)
Chitin is the second-largest polymer in world after cellulose, which can be broken down by chitinase enzymes. Microbes have great promise and sustainability in chitinase production at industrial level. The present study was aimed to produce and partially purify the chitinase from an endophytic bacterium Bacillus cereus CE3. The B. cereus CE3 was isolated from its host Coleus amboinicus. followed by improving the production medium by using one factor at a time, Plackett-Burman and response surface methodologies. Further, enzyme was purified by using various extraction and chromatographic techniques. The purified enzyme was analysed for its antifungal activities. The study revealed that B. cereus CE3 yielded three-fold chitinase when the variables like yeast extract, fermentation time, and orange peel powder were standardized during statistical optimization of medium, as suggested by Plackett-Burman and Response surface methodologies. In optimized medium the overall yield of chitinase enzyme was 44.87%, and the enzyme was purified three-fold by using precipitation, dialysis and column chromatography. The molecular weight of partially purified chitinase was 43 kDa as per SDS-PAGE analysis. The stability and efficiency of enzyme and its activity revealed that the enzyme was alkaline and mesophilic in nature. It showed antifungal activity by inhibiting the growth of Fusarium sp., and Aspergillus sp. The partially purified endophytic chitinase can be used as an active ingredient in cosmetics, pharmaceuticals, and agricultural products as a biocontrol agent.